Прагматизм податкоспроможності об’єднаних територіальних громад у контексті фіскальної децентралізації - Бойко, Світлана Василівна (My University, 2019)
У статті виконано емпіричний аналіз сучасного стану податкоспроможності об’єднаних територіальних громад у контексті забезпечення їх розвитку. Визначено середній індекс податкоспроможності бюджетів об’єднаних територіальних громад за формулою середньої арифметичної простої та зваженої у 2016-2019 роках та побудовано регресійні моделі, що дало можливість зробити висновок про позитивну динаміку середнього показника. Визначено дотаційність більшості бюджетів об’єднаних територіальних громад, високий рівень їх диференціації за рівнем індексу податкоспроможності та темпом його приросту. The reform of the administrative-territorial structure of Ukraine and the system of financial support of local self-government takes place taking into account the possibility of the formation of united territorial communities. Formation of united territorial communities took place in conditions of budget centralization, insufficient level of financial support and financing of expenses by transfers. Empirical study of the level of tax capacity of the budgets of the united territorial communities gave grounds for the conclusion about the growth of the average level of tax capacity of the budgets of the combined territorial communities. Changes in the level of tax capacity of the budgets of the united territorial communities occur slowly, which is confirmed by the value of the correlation coefficient of annual indicators. The structural changes in the distribution of the budgets of the united territorial communities by the index of tax capacity indicate the prevalence of the number of budgets, which is characterized by an increase in the index of tax capacity and a change in the order of horizontal equalization over budgets, which is characterized by a decrease in the index of tax capacity. The inverse relationship between the terms of existence of the united territorial communities and the rate of growth of the tax capacity index of their budgets is proved. The current state of distribution of the united territorial communities during their existence and the rate of growth of the tax capacity index has the following features: the budgets of the united territorial communities established in 2017 were the most heterogeneous in terms of the rate of growth of the index of tax capacity; the budgets of the united territorial communities established in 2015 and 2016 were homogeneous in terms of the rate of growth of the index of tax capacity. The average annual rate of growth of index of the tax capacity of the budgets of the united territorial communities was 6,2% (2015) and 9,3% (2016).
Keywords: бюджет; індекс податкоспроможності, об’єднані територіальні громади; дотації; децентралізація; budget; united territorial communities; decentralization; subsidies; index of tax capacity; кафедра фінансів